TEKNIK APROKSIMASI DALAM PERESTRUKTURAN KLAUSA EKSISTENSIAL: KASUS PENGINDONESIAAN NOVEL SERIAL HARRY POTTER KARYA J.K. ROWLING - Yan Mujiyanto (Sunan Kalijaga State Islamic University Yogyakarta, 2011)
This study aims to explain the implementation of approximation technique in clause restructuring to produce a target language text, which is functionally equivalent with its source language counterpart. It is deliberately designed to analyze existential clauses contained in an English novel along with its Indonesian translation. Four basic steps, which has been taken to process the data, are (1) data reduction, (2) data display, (3) data analysis, and (4) inference. It is revealed that a number of restructuring phases are employed to achieve functional equivalence. These phases are taken due to the fact that the basic elements of existential clauses in English do not have any one-to-one formal correspondence with their counterpart in Indonesian. Through approximation technique, existential clauses are then restructured according to their communicative or interactive functions. Clauses, which refers to existence, are restructured to form clauses on